Sociolinguistics in Scotland - Lawson, Robert; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Sociolinguistics in Scotland presents a comprehensive overview of sociolinguistic research in Scotland and showcases developments in sociolinguistic theory, method and application, highlighting Scotland's position as a valuable'sociolinguistic laboratory'. This book is a key resource for those interested in language use in Scotland.
Keywords: Linguistics; Historical linguistics; Sociolinguistics; Linguistics; Sociolinguistics; Historical Linguistics